Contemporary Perspectives on Three-Dimensional Facial Scanning in Clinical Dentistry: A Literature Review - Potapchuk, Анатолій; Almashi, Василь; Bretsko, Юрій (Actual Dentistry, 2026)
Accuracy and precision are key parameters in facial scanning within dentistry, as they determine the degree of correspondence between digital patient models and actual anatomical structures, as well as their suitability for diagnosis, treatment planning, implant fabrication, and postoperative evaluation. Achieving optimal scanning accuracy requires the application of advanced technologies combined with adherence to standardized procedural protocols. The accuracy and precision parameters of facial scanners largely depend on the device type, its technical characteristics, and the software used for data processing. The detailed influence of these factors is examined in the following sections. Objective: to analyze the current state of facial scanning technology in dentistry, outlining its historical development, operational mechanisms, and the available evidence regarding its applications and limitations within digital dentistry. Material and methods. Relevant publications related to the study topic were retrieved from scientific databases such as Scopus, PubMed, BVS, and SciELO, using the following keywords: facial scanner, dentistry, prosthodontics, virtual patient, maxillofacial prosthetics, accuracy. As a result, 84 relevant scientific publications were identified. The search depth covered the past five years, allowing for the analysis of the most current and significant data relevant to the study objective. The review included original research articles, study results, and official recommendations from medical associations. The inclusion criterion was the presence of positive outcomes in the investigated groups. The collected materials were analyzed in accordance with the principles of content analysis, followed by data systematization and classification using CADIMA software. Conclusions. Despite existing limitations related to scanning quality and software performance, three-dimensional facial scanners represent fast and non-invasive tools that can be effectively applied across various areas of dental practice. Facial scanners play an essential role in the digital workflow, providing facial records that enhance interdisciplinary communication, virtual articulation, smile design, and the diagnosis and management of obstructive sleep apnea. In the future, facial scanning technology demonstrates significant potential for applications in craniofacial research, as well as in prosthetic diagnostics and dental treatment planning.